2019
DOI: 10.3389/fmicb.2019.01857
|View full text |Cite
|
Sign up to set email alerts
|

Apical Trafficking Pathways of Influenza A Virus HA and NA via Rab17- and Rab23-Positive Compartments

Abstract: The envelope proteins of influenza A virus, hemagglutinin (HA) and neuraminidase (NA), play critical roles in viral entry to host cells and release from the cells, respectively. After protein synthesis, they are transported from the trans -Golgi network (TGN) to the apical plasma membrane (PM) and assembled into virus particles. However, the post-TGN transport pathways of HA and NA have not been clarified. Temporal study by confocal microscopy revealed that HA and NA colocalized soon aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Several researchers have engineered Influenza A viruses through reverse genetics to study different aspects of viral replication. These include insertion of Fluorescent or Bioluminescent reporters in to IAV structural proteins or expression of tetra cysteine or Sortase tags that allow chemical labelling of the viral protein for fluorescence-based detection [ 12 , 14 , 20 , 23 , 25 , 26 , 27 , 28 ]. Here, we focused on developing a reporter virus to achieve live imaging of HA dynamics in infected cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have engineered Influenza A viruses through reverse genetics to study different aspects of viral replication. These include insertion of Fluorescent or Bioluminescent reporters in to IAV structural proteins or expression of tetra cysteine or Sortase tags that allow chemical labelling of the viral protein for fluorescence-based detection [ 12 , 14 , 20 , 23 , 25 , 26 , 27 , 28 ]. Here, we focused on developing a reporter virus to achieve live imaging of HA dynamics in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by live imaging data, which showed reduced HA accumulation and translocation in presence of Tunicamycin. It has been reported that in polarized cells, HA transport occurs towards apical membrane [ 28 ]. In the live imaging experiment, we were able to observe lateral accumulation of HA at early time points, followed by apical transport at the late stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sparse information on ESCRTs functioning on polarized sorting, a significant body of data suggested apical and basolateral membrane proteins traffic through Rab-associated endosomal compartments to target the destinated membrane domain in polarized cells [29,[46][47][48][49][50]. Studies in rodents [8,29] and polarized WIF-B9 cell models [10,33] have demonstrated the apical targeting of BSEP traversed Rab11-positive endosomal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins then assemble with viral genomic segments. The virions are finally closed and M1 and M2 proteins mediate virion budding from the apical side of the cells [28,[95][96][97][98]. NA protein cleavages the SA residues, which allows the virions to be released from the plasma membrane [99].…”
Section: Life Cycle Of Influenza a Virusmentioning
confidence: 99%